Bond strength of CAD-CAM resin composite blocks cemented with flowable or pre-heated resin composites using different adhesive strategies - Contento-Fierro, Nathalie Cristina; Zúñiga-Mayhua, Eliam Cielo; Borda-Bizaga, Jorge Alonso; Besegato, João Felipe; Peñaherrera Manosalvas, María Soledad; Sanchez-Puetate, Cristian Fernando; Escalante-Otárola, Wilfredo Gustavo (Brazilian Dental Science, 2026)
Objective: To evaluate the bond strength of CAD-CAM resin composite blocks cemented with flowable or pre-heated resin composites using different adhesive strategies. Material and Methods: Seventy Brava Block (FGM) CAD-CAM resin composite cylinders were milled, and one surface was treated by 50 μm alumina sandblasting, followed by ultrasonic cleaning and 70% alcohol cleaning. The cylinders were distributed into seven groups: one control group using a light-cured resin cement (Variolink Esthetic LC), three with flowable composite resin (FR), and three with preheated composite resin (PR), applying different adhesive strategies. The cementing agents were light-cured (VALO Grand, 1200 mW/cm2 ) and specimens were stored at 37 °C for 24 hours. Bond strength was evaluated using shear testing (OM150, 1 mm/min), calculating average values and classifying fracture types. Data were analyzed using ANOVA and Tukey’s post hoc test (p